Esterification of Microwave Pyrolytic Oil from Palm Oil Kernel Shell - Sharifah Mona, Abdul Aziz; Rafeah, Wahi; Zainab, Ngaini; Sinin, Hamdan; Syamila Aimi, Yahaya (Hindawi Publishing Corporation, 2017)
Microwave pyrolysis is a potential for producing alternative fuel from biomass, such as palm kernel shell (PKS). However, the resulting microwave pyrolytic oil (bio-oil) was highly acidic and has low calorific value and therefore must undergo additional process to improve the physicochemical properties. In this study, attempt wasmade to improve the pH and calorific value of bio-oil produced from PKS via esterification process. The effect of esterification with ethanol in the presence of sulphuric acid as a catalyst on selected biodiesel qualities was also investigated. The esterification process has successfully improved the pH value from 3.37 to 5.09–5.12 and the calorific value was increased from 27.19 to 34.78–41.52MJ/kg. Conclusively, the EO has comparatively better properties in terms of its smell, pH, calorific value, and absence of environmentally undesirable compounds.However, future works should include ASTM 6751 specifications tests for biodiesel to evaluate the bio-oil’s suitability for commercial use.